THE POWER OF SPEECH ACTS IN DEMONIC EXORCISM PRAYERS FROM THE POPE'S EXORCIST (2023) - Kilen, Kevin Georgy; Anggraeni, Diana; Sigalingging, Bob Morison (Universitas Gunadarma, 2025)
This research analyzes the exorcism dialog in the film The Pope's Exorcist (2023), especially the prayers uttered by the main character in the exorcism ritual. The purpose of this research is to describe the speech acts elements in the exorcism prayers using Austin's (1962) speech acts theory which includes locutionary, illocutionary, and perlocutionary, so as to explain whether the utterances in the exorcism prayers are constative or performative according on their respective characteristics. The method used in this research is descriptive qualitative with pragmatics analysis approach. Data in the form of exorcism prayers excerpts were analyzed based on the three main elements of speech acts. The results show that locutionary act reflect the typical structure of general prayers and exorcism prayers in the Catholic Church's faith. Illocutionary act function as commands, requests, and declaratives that reflect the spiritual authority of the exorcist. While perlocutionary act have an impact on demon and the possessed individual. Overall, exorcism prayers tends to be performative in nature as it not only conveys meaning (constative), but also acts visibly in the context of religious rituals. This research contributes to the study of pragmatic linguistics in religious-horror films and provides insight into the use of language in the context of religious rituals, especially in the case of exorcism.